Prevalence and characterization of undiagnosed arterial hypertension in the eastern zone of Mexico - Silvia Palomo‐Piñón; Neftali Eduardo Antonio‐Villa; Luis Rey García‐Cortés; Cleto Álvarez‐Aguilar; Esteban González‐Palomo; Olga Margarita Bertadillo‐Mendoza; María Eugenia Figueroa‐Suárez; Francisco Vargas‐Hernández; Imer Guillermo Herrera‐Olvera; Jairo Enoc Cruz‐Toledo; Maria Adriana Cruz‐Arce; Berenice Serafín‐Méndez; et al. (The Journal of Clinical Hypertension, 2022)
Abstract Arterial hypertension is considered a public health problem with severe consequences at an individual and public health levels. However, there is a lack of information regarding its characterization in Mexico. The objective of this study is to estimate the proportion of undiagnosed arterial hypertension (UAH) and the overall prevalence and clinical management of arterial hypertension within the Eastern Zone of Mexico. Additionally, we explore associated factors related with both UAH and uncontrolled arterial hypertension. We obtained information from the May Measure Month (MMM) 2019 study. People were asked for cardiovascular risk factors and blood pressure was measured according to the protocols of the European Society of Hypertension (ESH). Data from 5901 subjects were extracted: 76.04% from the Eastern Zone of the State of Mexico. The overall prevalence of hypertension was 32.4% (95% CI 31.2‐33.6). From all subjects living with hypertension, 28.3% had UAH, 22.1% had previous diagnosis but were untreated; 29.3% were treated but had uncontrolled hypertension. Younger men adults living in the State of Michoacán had increased proportion of UAH and untreated hypertension. We observed that male sex, age, obesity, living at Michoacán were risk factors for UAH. Finally, male sex, diabetes, and living at Michoacán were related risk conditions for having uncontrolled arterial hypertension. In summary, there is a high proportion of UAH in Easter Zone of Mexico. Younger adults had higher proportion of UAH and untreated hypertension profiles. Efficient actions are required to make a timely diagnosis in the young adult population to prevent long‐term complications.